The effects of economic policy uncertainty on European economies: Evidence from a TVP-FAVAR - Jan Prüser; Alexander Schlösser (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Recent events such as the financial and sovereign debt crisis have triggered an increase in European Economic Policy Uncertainty (EPU). We use a TVP-FAVAR model with hierarchical priors on the hyperparameters to investigate the effect of EPU on a wide range of macroeconomic variables for eleven European Monetary Union (EMU) countries. First, we find that EPU shocks are transmitted through various channels, such as the real options-, the precautionary savings- and the financial channel. Second, we are able to distinguish between a group of fragile countries (GIIPScountries) and a group of stable countries (northern countries), where the former are more strongly affected by EPU shocks. Third, while the IRFs for most variables differ only in magnitude and not in sign between groups of countries, responses of long term interest rates to EPU shocks have a different sign across countries. Fourth, we discover that investors and traders react more sensitively than consumers to uncertainty. Fifth, we find that EPU shocks affect monetary policy decisions. Sixth, we provide evidence that the transmission of EPU shocks is quite stable over time. Finally, the increase in EPU can partly be explained by the state of the European economy and should therefore be treated as an endogenous variable. – – Jüngste Ereignisse wie die Finanz- und Staatsschuldenkrise in Europa gingen mit einem Anstieg der wirtschaftspolitischen Unsicherheit (EPU) einher. Um die Effekte von EPU auf neun makroökonomische Variablen für elf Länder der Europäischen Währungsunion zu quantifizieren, verwenden wir ein TVP-FAVAR Modell mit hierarchischen Prioren. Unsere Studie zeigt erstens, dass EPU über verschiedene Kanäle, wie dem realen Options-, dem vorsorglichen Spar- und dem Finanzkanal, übertragen wird. Zweitens, basierend auf den Impuls-Antwort-Folgen (IAF) können wir zwischen den GIIPS-Ländern und den nördlichen Ländern unterscheiden, wobei erstgenannte stärker von EPU-Schocks beeinflusst werden. Drittens, während sich die IAF für acht Variablen lediglich in der Stärke und nicht im Vorzeichen unterscheiden, gibt es in jenen der langfristigen Zinsen auf Staatsanleihen Unterschiede im Vorzeichen. Viertens zeigt unsere Studie, dass Investoren stärker auf EPU-Schocks reagieren als Konsumenten. Fünftens, wir zeigen, dass EPU die gemeinsame europäische Geldpolitik beeinflusst. Sechstens liefert unsere Studie empirische Belege dafür, dass der Transmissionsmechanismus von EPU-Schocks über die Zeit konstant ist. Schlussendlich geht aus unserer Studie hervor, dass der Anstieg von EPU teilweise durch die aktuelle wirtschaftliche Lage der europäischen Volkswirtschaften erklärt werden kann, weshalb EPU als endogene Variable behandelt werden sollte.
Keywords: C11; C32; E20; E60; 330; TVP-FAVAR; economic policy uncertainty; fat data; hyperparameter; European Monetary Union; hierarchical prior